Re-restoration of the sgraffito facades of the Entrance Tower of the Litomyšl Chateau - Vojtěchovský, Jan (Univerzita Pardubice, 2022)
The paper is devoted to the presentation of the sgraffito decoration the Entrance Tower of the Litomyšl Chateau. The sgraffito dates back to the 1730s and is a curious example of this technique at a time when it was already out of fashion. The façade underwent a rich development in different periods of time, which usually did not respect not only the sgraffito itself, but also the formal structure of the façade. Several waves of restoration of the façade subsequently took place in the 20th century, with the most complex being carried out in the late 1970s and early 1980s. This intervention set a completely new perception of the façade, combining the original elements of the façade with a visually very different Baroque reconstruction and completely new additions in the style of the original. The text reflects on the appropriateness of this approach and its defensibility in the context of generally accepted conservation conventions (e.g. the Venice Charter), both then and now. The text also presents the restoration intervention on the sgraffito decoration of the Entrance Tower of the Litomyšl Chateau from 2014-2015, during which findings from the history and development of the facades in question were collected. The paper explains why the concept from the late 1970s and early 1980s was more or less respected during the latest intervention.
Re-restaurování sgrafitových fasád vstupní věže zámku v Litomyšli
Keywords: re-restoration; conservation; sgraffito; sgraffito façade; concept of conservation; reconstruction; Litomyšl Chateau; re-restaurování; konzervování; sgrafito; sgrafitová fasáda; koncepce restaurování; rekonstrukce; zámek v Litomyšli